Mucin-type O-glycans and their roles in intestinal homeostasis - Bergstrom, Kirk S B (Oxford University Press, 2013)
Mucin-type O-glycans are the primary constituents of mucins that are expressed on various mucosal sites of the body, especially the bacteria-laden intestinal tract. Mucins are the main components of mucus, which is secreted by goblet cells and forms a protective homeostatic barrier between the resident microbiota and the underlying immune cells in the colon. However, the specific role of mucin-type O-glycans in mucus barrier function has been uncertain. Recent studies utilizing mice deficient in key glycosyltransferases involved in O-glycan biosynthesis on intestinal mucins have underscored the importance of mucin-type O-glycosylation in mucus barrier function. This review will highlight recent advances in our understanding of mucin-type O-glycan function in the mucus barrier and how they promote mutualism with our resident microbiota.